Effect of heat stress on crossbred dairy cattle in tropical Nepal: Impact on blood parameters - Paudel, Tulasi Prasad; Acharya, Buddhi Ram; Karki, Dainik Bahadur; Shrestha, Bhola Shankar (Journal of Agriculture and Natural Resources, 2018)
Chitwan district of Nepal has been known as the dairy kingdom of the country considering its strategic location andpotential to easily provision inputs and produce as well as market quality milk across the country. However, theclimate especially during summer has been a challenge to farmers that potentially compromise the daily milk yieldof cows. Therefore, sixteen crossbred dairy cattle were placed in a RCBD fashion to assess the impacts of cold waterbathing in ameliorating effect of heat stress on their performance and body physiology. Routine assessment of themicroclimate within the experimental shed and blood parameters was made. The results from the experimentinferred that frequency of bathing (none, once, twice or thrice a day) did not have any significant impact onHaemoglobin, Haematocrit, Sodium, Potassium, Chloride and Bicarbonate levels in the blood plasma(p>0.05). Inaddition, the animals did not exhibit any signs of physiological distress clinically either. A detailed study scopingtemperature humidity index and over a number of other milk and blood parameters are to be tested across a numberof other available breeds too in order for the researchers to come to a meaningful strategy to beat the heat stress.